Koli women selling fish in a nearby street market - Mumbai Archive Project Team (Jio Institute, 2024)
Historically, Koli women used to sell fish caught from nearby water bodies like the Mithi River. Today, most of these water bodies are either heavily polluted or have been developed over, making the fishing business unsustainable. The majority of fish sold in local markets now comes from wholesale markets in South Mumbai.